2010
DOI: 10.1111/j.1476-4431.2010.00564.x
|View full text |Cite|
|
Sign up to set email alerts
|

Case Report: Use of a nanocrystalline silver dressing and vacuum‐assisted closure in a severely burned dog

Abstract: VAC and NSD were used successfully for the treatment of a severe burn injury in a dog. The use of NSD decreased the cost of therapy by reducing the need for daily bandage changes, thereby reducing the anesthetic and analgesic costs and allowing the patient to be managed on an outpatient basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…, Mullally et al . , Demaria et al . ), however, only three studies describe its application to wounds of the distal appendicular skeleton and none of these reports includes its use over metallic implants (Argenta et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Mullally et al . , Demaria et al . ), however, only three studies describe its application to wounds of the distal appendicular skeleton and none of these reports includes its use over metallic implants (Argenta et al .…”
Section: Discussionmentioning
confidence: 99%
“…As compared with the conventional wet-to-dry (Demaria et al 2011) or foam (Morykwas et al 2001, Chen et al 2005 dressings, application of sub-atmospheric pressures to wounds has been shown to assist in restoration of capillary basement membrane integrity, promotion of granulation tissue formation and improvements in local microcirculation (Chen et al 2005). Different applications of VAC therapy have been reported in veterinary medicine (Ben-Amotz et al 2007, Guille et al 2007, Lafortune et al 2007, Kirkby et al 2010, Mullally et al 2010, Demaria et al 2011, however, only three studies describe its application to wounds of the distal appendicular skeleton and none of these reports includes its use over metallic implants (Argenta et al 1997, Ben-Amotz et al 2007, Lafortune et al 2007. Exposed metal has been shown to be associated with higher rates of infection and difficulties in wound management…”
Section: Discussionmentioning
confidence: 99%